Synthetic light-curable polymeric materials provide a supportive niche for dental pulp stem cells - Vining, Kyle H.; Scherba, Jacob C.; Bever, Alaina; Alexander, Morgan R.; Celiz, Adam D.; Mooney, David J. (Wiley, 2018)
Dental disease annually affects billions of patients, and while regenerative dentistry aims to heal dental tissue after injury, existing polymeric restorative materials, or fillings, do not directly participate in the healing process in a bioinstructive manner. There is a need for restorative materials that can support native functions of dental pulp stem cells (DPSCs), which are capable of regenerating dentin. A polymer microarray formed from commercially available monomers to rapidly identify materials that support DPSC adhesion is used. Based on these findings, thiol-ene chemistry is employed to achieve rapid light-curing and minimize residual monomer of the lead materials. Several triacrylate bulk polymers support DPSC adhesion, proliferation, and differentiation in vitro, and exhibit stiffness and tensile strength similar to existing dental materials. Conversely, materials composed of a trimethacrylate monomer or bisphenol A glycidyl methacrylate, which is a monomer standard in dental materials, do not support stem cell adhesion and negatively impact matrix and signaling pathways. Furthermore, thiol-ene polymerized triacrylates are used as permanent filling materials at the dentin-pulp interface in direct contact with irreversibly injured pulp tissue. These novel triacrylate-based biomaterials have potential to enable novel regenerative dental therapies in the clinic by both restoring teeth and providing a supportive niche for DPSCs.